PENERAPAN TEKNIK SPOTLIGHT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 8 SAWAHLUNTO TAHUN PELAJARAN 2013/2014 - Sari, Rosy Ana Kartika; Nst, Minora Longgom; Yunita, Alfi (Pendidikan Matematika, 2013)
This research is motivated by the studentâs of mathematical concepts is low, one of the solution applying technique spotlight. The purpose of the researching to know did studentâs mathematic concept comprehension by applying technique spotlight better than studentâs mathematic concept by using conventional studying class VIII SMPN 8 Sawahlunto 2013-2014 school year. This type of research is experimental. Population is all students in grade VIII SMPN 8 Sawahlunto 2013-2014 school year. Technique of random sampling, VIII1 as experimental class and VIII 2 as control class.instrument of this research is post test in essai. The relibiatation of post testÂ  is 0,77. Technique of data analysis was T-test by using MINITAB softaware. Based on the result of data analyisis at Â got P-value 0,004. The P-value less than Â it can be concluded studentâs mathematic concept comprehension by applying technique spotlight better than studentâs mathematic concept by using conventional studying class VIII SMPN 8 Sawahlunto 2013-2014 school year.